A clinician's guide to rheumatic diseases in children - Lehman, Thomas J. A. (Oxford University Press, 2009)
In the United States alone, roughly 300,000 children suffer from some form of arthritis or rheumatic disease, and millions more are at risk of developing one of these diseases. In this marvelously down-to-earth guide, Thomas Lehman--the head of one of the leading pediatric rheumatology programs in the world--offers a gold mine of expert advice invaluable for pediatricians who want to become more proficient in understanding, diagnosing, and treating rheumatic disease in children. Dr. Lehman helps pediatricians interpret their patients' complaints and determine whether and what type of medical a.